Active muscle and tendon stiffness of plantar flexors in sprinters - Kubo, K.; Miyazaki, D.; Ikebukuro, T.; Yata, H.; Okada, M.; Tsunoda, N. (Journal of Sports Sciences, 2017)
The aim of the present study was to investigate and compare muscle and tendon stiffness under active conditions in sprinters and untrained participants. In total, 14 sprinters and 24 untrained men participated in this study. Active muscle stiffness in the medial gastrocnemius muscle was calculated based on changes in estimated muscle force and fascicle length during fast stretching after submaximal isometric contractions. Tendon stiffness was determined during isometric plantar flexion using ultrasonography. No significant differences were observed in active muscle stiffness between sprinters and untrained men at any torque levels. Furthermore, no significant difference was noted in tendon stiffness between the two groups. These results suggest that muscle and tendon mechanical properties in the plantar flexors under active conditions are similar in sprinters and untrained participants